1992
DOI: 10.1128/mcb.12.5.2124
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism and consequences of the duplication of the human C4/P450c21/gene X locus.

Abstract: The adjacent C4 and P450c21 genes encode the fourth component of serum complement and steroid 21-hydroxylase respectively, and are tandemly duplicated in the human, murine, and bovine genomes. We recently cloned a cDNA for another duplicated gene, operationally termed X, which overlaps the 3' end of human P450c21 and has the opposite transcriptional orientation. Thus, the organization of the locus is 5'-C4A-21A-XA-C4B-21B-XB-3' (Y. Morel, J. Bristow, S. E. Gitelman, and W. L. Miller, Proc. Natl. Acad. Sci. USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…Restrictin can promote cell adhesion of neural cells, but does not promote neurite extension (Rathjen et al, 1991). No functional data are available yet on the human tenascin-X gene, which is prominently expressed in fetal muscle and testis and at lower levels in fetal adrenal gland, kidney and lung (Gitelman et al, 1992;Bristow et al, 1993). However, it has been suggested that this gene has an essential function, since many cases of adrenal hyperplasia have been traced to gene deletions in close proximity to, but never within, the tenascin-like gene (Bristow et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Restrictin can promote cell adhesion of neural cells, but does not promote neurite extension (Rathjen et al, 1991). No functional data are available yet on the human tenascin-X gene, which is prominently expressed in fetal muscle and testis and at lower levels in fetal adrenal gland, kidney and lung (Gitelman et al, 1992;Bristow et al, 1993). However, it has been suggested that this gene has an essential function, since many cases of adrenal hyperplasia have been traced to gene deletions in close proximity to, but never within, the tenascin-like gene (Bristow et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Human P450c21 is encoded by the CYP21B gene, which lies in a complex array of genes on chromosome 6p21.3. The human (8 -10), bovine (11,12), and rodent (13,14) genomes have duplicated CYP21A and CYP21B genes, but these duplications postdate mammalian speciation and have different duplication boundaries (15). Only the human 21B gene encodes P450c21, as the 21A gene carries three mutations that destroy the reading frame (8 -10).…”
Section: Congenital Adrenal Hyperplasia (Cah)mentioning
confidence: 99%
“…1). The 5Ј ends (transcriptional start sites) of the human CYP21A and CYP21B genes lie only 2466 bp downstream from the polyadenylation sites of the corresponding C4A and C4B genes (15,18).…”
Section: Congenital Adrenal Hyperplasia (Cah)mentioning
confidence: 99%
See 1 more Smart Citation
“…TNXA is a partially duplicated gene segment that corresponds to intron 32 to exon 45 of TNXB. In addition, there is a 120-bp deletion at exon 36-intron 36 that results in a frameshift mutation and premature termination of translation (30,40).…”
mentioning
confidence: 99%